Sequences polymorphism and variation of major histocompatibility complex DRB exon 2 of black Dahe pig - Lizhou Tang; Long Yu , Jiangang Chen , Junjie Wang , Mei Ma , Weidong Lu; Tongzuo Zhang (African Journal of Pig Farming, 2019)
DNA sequences of swine leukocyte antigens (SLA) DRB exon 2 from five populations were used to investigate genetic polymorphism of black Dahe pig in Yunnan province of China. Our results showed that the SLA-DRB exon 2 of black Dahe pig obtained high variable rate of 23.50%, which was higher than the values analyzed for cattles or other livestocks. The average G + C content at the third synonymous variable coding positions (GC3) was closed to 0.78. The amino acids composition rate and majority of relative synonymous codon usage were near the ranges of 0.00 to 11.27 and 1.00 to 2.00, respectively. These significant polymorphism, high GC3 content and differentiation of preferred codon usage could be resulted from over dominance selection, base compositional bias and the diversity of gene expression level. Aforementioned results adequately testified the SLA-DRB exon 2 may be an important genetic marker for studies in genetic diversity, population genetics, breeding reproduction investigation and exploring new functional genes of black Dahe pig.